Recent Biomimetic and Organocatalytic Syntheses of ?-Tocopherol - Antoinette Chougnet; Kegang Liu; Wolf-D. Woggon (CHIMIA, 2010)
We report here on our efforts to develop new strategies for the synthesis of ?-tocopherol, the biologically most significant member of the vitamin E family. This review comprises five new methods to generate the chiral chromane of ?-tocopherol with overall up to 29% yield from commercially available material and up to 94% de.